Swami Chinmayananda - Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2022)
Nurtured on modern learning and ancient wisdom as a child, he taught himself to meditate even as he dreamed of dinner, skipped out of family visits to the temple but spent hours in solitary prayer, and campaigned for India's freedom while aiming for a master's degree in English literature. 'Chinmaya' means true knowledge, and it is what Swami Chinmayananda taught the world.
Keywords: Fables; Humour; Biography- Swami Chinmayananda(1916-1993)